(untitled) (Annals of Medical Research, 2021)
Aim: Although there is a gold standard liver biopsy in showing the histological activity of the disease, there are contradictory results in the studies conducted for using some non-invasive methods that are alternatively biochemically calculated due to being an invasive procedure. We aimed to investigate the relationship of FIB-4, APRI, API and AAR values with histopathology in patients undergoing liver biopsy due to chronic hepatitis B virus (HBV) infection. Materials and Method: Patients with follow-up between November/2016-October/2019 with the diagnosis of chronic HBV were included. Demographic data and histopathological data were documented. Accompanying comorbid diseases, medications and previous operations were questioned. Patients were grouped as mild, moderate and advanced fibrosis according to fibrosis scoring. Sensitivity, specificity, cutt-of, AUC values of biochemical parameters were calculated between the groups. Results: A total of 151 patients, 64(42.3%) women, were included in the study. As a result of the liver biopsy; mild fibrosis was found in 73(48.3%) patients, moderate fibrosis in 33(21.8%) patients and advanced fibrosis in 45(29.9%) patients. There was a significant correlation between fibrosis level and age, liver function tests, bilirubin and albumin (p<0.05). While there was no relationship between fibrosis stage and HBV-DNA, there was a significant relationship between groups with AAR, API, APRI and FIB4 (p<0.05). Conclusions: Although FIB-4, APRI, AAR and API values are important in determining the level of hepatic fibrosis, the effect of biochemical parameters on various factors negatively affects the specificity and sensitivity of these tests. For this reason, liver biopsy is still seen as the gold standard.